2009
DOI: 10.1371/journal.pone.0007122
|View full text |Cite
|
Sign up to set email alerts
|

Compartmentalization of HIV-1 within the Female Genital Tract Is Due to Monotypic and Low-Diversity Variants Not Distinct Viral Populations

Abstract: BackgroundCompartmentalization of HIV-1 between the genital tract and blood was noted in half of 57 women included in 12 studies primarily using cell-free virus. To further understand differences between genital tract and blood viruses of women with chronic HIV-1 infection cell-free and cell-associated virus populations were sequenced from these tissues, reasoning that integrated viral DNA includes variants archived from earlier in infection, and provides a greater array of genotypes for comparisons.Methodolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
59
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(66 citation statements)
references
References 55 publications
6
59
1
Order By: Relevance
“…† Storey and Tibshirani (25) q value from SM P value, shown in bold, where q < 0.05. (18) for seminal PL and consistent with other studies that have investigated the relationship between blood and genital viral populations (5,(17)(18)(19)(20)(21). If transmission were a stochastic sampling of the donor GT virus population, the most common viral variants in the donor GT should have the greatest opportunity to interact with the recipient genital mucosa and be favored for transmission.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…† Storey and Tibshirani (25) q value from SM P value, shown in bold, where q < 0.05. (18) for seminal PL and consistent with other studies that have investigated the relationship between blood and genital viral populations (5,(17)(18)(19)(20)(21). If transmission were a stochastic sampling of the donor GT virus population, the most common viral variants in the donor GT should have the greatest opportunity to interact with the recipient genital mucosa and be favored for transmission.…”
Section: Discussionsupporting
confidence: 79%
“…Recent studies have begun to answer the question of whether viral variants are sequestered in the genital tissue (17)(18)(19)(20)(21)(22) and show that distinct genetic lineages can propagate there. Here, we studied the genetic relationship of viruses in the blood and genital fluids from the chronically infected donor partners of eight Rwandan and Zambian transmission pairs and show that although distinct viral subpopulations are present in the GT, the transmitting founder variant did not originate from the predominant sampled population.…”
mentioning
confidence: 99%
“…Each of the subjects with evidence of significant compartmentalization by both tests had a large number of identical or nearly identical sequences in milk (Table 3), which could contribute to an overestimation of potential compartmentalization (6,7,15). Therefore, the identical sequences within the same compartment were removed from the data set subjected to the SM and S nn analyses for all subjects.…”
Section: Resultsmentioning
confidence: 99%
“…Divergent mucosal immune responses may shape compartmentspecific viruses, as described for anatomic compartments such as semen and cervicovaginal fluid (2,6,9,11,21,22,37). Early investigations of whether breast milk virus variants were compartmentalized from those in plasma were contradictory (5,16).…”
mentioning
confidence: 99%
“…Several studies have reported compartmentalization of viral sequences in the FMTwithin at least a subset of subjects (Poss et al 1998;Kemal et al 2003;Adal et al 2005;Andreoletti et al 2007). More recently, this compartmentalization was interpreted to be largely the result of clonal amplification (Bull et al 2009). There is a need for both longitudinal analysis of viral populations within the genital tract, and an examination of the impact of concurrent localized bacterial infections with attendant inflammation.…”
Section: Genital Tractmentioning
confidence: 99%